2017
DOI: 10.1186/s12888-016-1160-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of atopic dermatitis with depressive symptoms and suicidal behaviors among adolescents in Korea: the 2013 Korean Youth Risk Behavior Survey

Abstract: BackgroundAtopic dermatitis (AD) is a chronic skin disease which has been known to negatively influence the mental health of patients. However, only a few studies have explored the prevalence of psychiatric problems among AD patients, particularly among adolescents. In this study, we aimed to assess the association of AD with depressive symptoms and suicidal behaviors among adolescents by analyzing data from the 2013 Korean Youth Risk Behavior Survey, a nationwide web-based survey.MethodsData from 72,435 adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 50 publications
5
70
2
1
Order By: Relevance
“…Our effect estimates for asthma were comparable with other studies using cohorts of comparable age . In regard to the other atopic diseases, although less studied than asthma, our study contributes to the growing body of epidemiological evidence finding that eczema, food allergy and rhinitis are each associated with depression or anxiety in children.…”
Section: Discussionsupporting
confidence: 84%
“…Our effect estimates for asthma were comparable with other studies using cohorts of comparable age . In regard to the other atopic diseases, although less studied than asthma, our study contributes to the growing body of epidemiological evidence finding that eczema, food allergy and rhinitis are each associated with depression or anxiety in children.…”
Section: Discussionsupporting
confidence: 84%
“…Notably, a large recent Taiwanese study found that adolescents with AD had a stronger risk of anxiety than depression, whereas the risk of depression was stronger compared to anxiety in adults . Moreover, a recent study of adolescents from Korea found slightly increased risks of suicidal ideation, planning, and attempts in patients with AD . It is possible that a “psychiatric march” exists in patients with AD, where chronic pruritus, sleep disturbance, and poor self‐esteem in turn may lead to anxiety, depression, and possibly even suicide …”
Section: Introductionmentioning
confidence: 99%
“…11 Eczema was also associated with social isolation in a sample of 54 adults from the United Kingdom. 12 The majority of data on mental health or psychosocial burden in AE comes from the United States and from Asian adult populations [13][14][15][16][17][18][19][20][21][22][23][24][25] ; only a few data exist from continental Europe 1, [26][27][28] and even less from Germany. Currently available data on adults with AE from Germany rely on selected cohorts of patients, 1,[28][29][30][31] including health insurance data.…”
Section: Introductionmentioning
confidence: 99%